2020
DOI: 10.1080/19390211.2020.1790708
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Cannabinoids and their Role in Modulation of Cardiovascular Health

Abstract: In recent years, the role of the endocannabinoid system (ECS) in various cardiovascular conditions has been a subject of great interest. The ECS is composed of cannabinoid receptors, their endogenous ligands, also known as endocannabinoids, and enzymes responsible for the synthesis and degradation of endocannabinoids. Several lines of evidence suggest that the ECS plays a complex role in cardiac and vascular systems; however, under normal physiological conditions the functions of the ECS are limited. Overactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 139 publications
(148 reference statements)
1
6
0
Order By: Relevance
“…Using the formula “rat dose = human dose ∙ 6.2” ( Nair and Jacob, 2016 ), a rat dose range 6.2–310 mg/kg/day was obtained. In mice and rats, the most used repetitive administration regimens consisted of 10 mg/kg/day CBD, i. p. Or per os, for 1–6 weeks(s) ( Wheal et al, 2017 ; Karimian Azari et al, 2020 ). Interestingly, i. p. And oral routes were found to result in similar concentrations in the rat (both in the plasma and brain) ( Deiana et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using the formula “rat dose = human dose ∙ 6.2” ( Nair and Jacob, 2016 ), a rat dose range 6.2–310 mg/kg/day was obtained. In mice and rats, the most used repetitive administration regimens consisted of 10 mg/kg/day CBD, i. p. Or per os, for 1–6 weeks(s) ( Wheal et al, 2017 ; Karimian Azari et al, 2020 ). Interestingly, i. p. And oral routes were found to result in similar concentrations in the rat (both in the plasma and brain) ( Deiana et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was not possible to assess this directly in the current study due to the time at which samples were taken (4 h post poly I:C administration). Alternatively, PEA may mediate its effects by modulating cardiovascular or metabolic pathways ( Karimian Azari et al, 2020 ; Mattace Raso et al, 2014 ) involved in thermoregulation. Further studies will be required to examine the mechanisms by which PEA is mediating its inhibitory effects on the poly I:C-induced fever response.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the myocardial CB 1 receptor results in a negative inotropic effect – diminishing myocardial contractility, as well as lowering blood pressure, 11 , 12 whereas activation of these receptors in vascular endothelial cells leads to vasodilation and participates in the process of proliferation and migration of vascular smooth muscle cells ( Figure 2 ). 11 , 13 In contrast, the CB 2 receptor is mainly expressed on blood cells and immune tissues, and its activation is involved in the regulation of immune cell function, for instance, controlling acute inflammatory response. 14 Recent studies have also demonstrated the expression of CB 2 receptor within the cardiovascular system, namely, rat cardiomyocytes 15 and human endothelial cells, 16 , 17 in which it was shown that its activation plays a cardioprotective role, especially in postischemic reperfusion injury.…”
Section: The Ecsmentioning
confidence: 99%